Simply blending Ni nanoparticles with typical photocatalysts for efficient photocatalytic H2 production. Issue 24 (26th November 2019) - Cheng, Cheng; Shi, Jinwen; Du, Fan; Zong, Shichao; Guan, Xiangjiu; Zhang, Yazhou; Liu, Maochang; Guo, Liejin
Abstract : A photocatalytic system construction method of simply blending as-prepared Ni nanoparticles (Ni NPs) with g-C3 N4 was carried out to greatly improve the photocatalytic activity of g-C3 N4 . Abstract : A photocatalytic system construction method of simply blending as-prepared Ni nanoparticles (Ni NPs) with g-C3 N4 was carried out to greatly improve the photocatalytic activity of g-C3 N4 . In the photocatalytic H2 production process, Ni NPs were not anchored on the surface of g-C3 N4, but they existed in the reaction solution as freestanding nanoparticles; the continuous and frequent collision-contact between Ni NPs and g-C3 N4 could efficiently promote the migration of photogenerated charges of g-C3 N4, leading to an enhanced photocatalytic H2 -production activity. Moreover, this simple blend method can be applied to other photocatalysts (such as TiO2 and CdS), and this blend method provides a simple, repetitive and generally applicable way to build a noble-metal-free photocatalytic system for the efficient photocatalytic H2 -production activity of the photocatalyst with Ni as the cocatalyst.